Vitamin D and Breast Cancer: Past and Present - Welsh, JoEllen (J Steroid Biochem Mol Biol, 2017)
The presence of the vitamin D receptor in mammary gland and breast cancer has been recognized since the early 1980s, and multiple pre-clinical studies have demonstrated that its ligand 1,25D modulates normal mammary gland development and sensitivity to carcinogenesis. Although studies have characterized many 1,25D responsive targets in normal mammary cells and in breast cancers, validation of relevant targets that regulate cell cycle, apoptosis, autophagy and differentiation, particularly in vivo, has been challenging. Vitamin D deficiency is common in breast cancer patients and some evidence suggests that low vitamin D status enhances the risk for disease development or progression. Model systems of carcinogenesis have provided evidence that both VDR expression and 1,25D actions change with transformation but clinical data regarding vitamin D responsiveness of established tumors is limited and inconclusive. Because breast cancer is heterogeneous, analysis of VDR actions in specific molecular subtypes of the disease is necessary to clarify the conflicting data. Genomic, proteomic and metabolomic analyses of in vitro and in vivo model systems is also warranted to comprehensively understand the network of vitamin D regulated pathways in the context of breast cancer heterogeneity.